Global trends and regional differences in disease burden of stroke among children: a trend analysis based on the global burden of disease study 2019 - Min Du; Donghua Mi; Min Liu; Jue Liu (BMC, 2023)
Abstract Background Stroke is a major cause of acute neurological symptoms in children with significant long-term neurological sequelae. However, data of diseases burden on stroke among children was lack. We aimed to be dedicated to analyze and compare global trends as well as regional and sociodemographic differences in stroke prevalence, incidence, mortality and disability-adjusted life-years (DALYs) among children aged 0 ~ 14 years. Method We obtained data on annual number of incident strokes, prevalent strokes, deaths, and DALYs, age-standardized incidence rates (ASIRs), prevalence rates (ASPRs), mortality rates (ASMRs) and DALY rates (ASDRs) of stroke among individuals aged 14 years and younger during 1990-2019 from the 2019 Global Burden of Disease Study. To quantify the temporal trends, we calculated changes (%) in number, and used joinpoint regression analysis to identify the average annual percentage changes (AAPCs) of age standardized rates. Result Globally, the incident strokes and prevalent strokes increased by 18.51% and 31.97%, respectively, but DALYs due to stroke and deaths due to stroke decreased by 60.18% and 65.03%, respectively, from 1990 to 2019. During the same period, ASIR increased by 0.21% (95%CI: 0.17, 0.24) from 18.02 to 100,000 population in 1990 to 19.11 per 100,000 in 2019; ASPR increased by 0.66% (95%CI: 0.36, 0.96) from 68.88 to 100,000 population in 1990 to 81.35 per 100,000 in 2019; while ASMR (AAPC= -3.94; 95%CI: -4.07, -3.81) and ASDR (AAPC= -3.50; 95%CI: -3.64, -3.36) both decreased. In 2019, the highest age standardized incidence, prevalence, mortality, and DALY rates all occurred in low sociodemographic index (SDI) regions. The greatest increase of age standardized incidence rate (AAPC = 0.21; 95%CI: 0.18, 0.25) and prevalence rate (AAPC = 1.15; 95%CI: 0.34, 1.96) both were in high SDI regions. Eastern Sub-Saharan Africa had the highest ASIR and ASPR in 2019, and Oceania had the highest ASMR and ASDR in 2019 across 21 GBD regions. High-income North America had the largest increase in ASIR (AAPC = 0.63; 95%CI: 0.59, 0.66) and ASPR (AAPC = 1.58; 95%CI: 0.54, 2.63). Against the overall decreasing trend of ASMR, an increasing trend of ASMR was found in Zimbabwe (AAPC = 0.91; 95%CI: 0.44, 1.37) and Botswana (AAPC = 0.74; 95%CI: 0.02, 1.47). Conclusion The overall increasing stroke incidence and prevalence indicated that prevention and management of stroke among younger population should be critical in the future. Despite stroke mortality with falling trend worldwide, specific countries or territories present worrying increase in stroke mortality. Without urgent implementation of effective primary prevention strategies, the stroke burden of children will probably continue to grow across the world, particularly in high-SDI countries.